Transformasi Narasi Anak Indigo dalam Komposisi Musik Nusantara Berbasis Pendekatan Eksperimental-Kontemporer - Ibrahim Lubis; Rizki Mona Dwi Putra; Rezki Aulia; Afdal Anas (Grenek: Jurnal Seni Musik, 2026)
"Indigo" composition music is a kind of music that inspired by indigo phenomenon. They are a kid who are generally difficult to manage by power, hard to compromise, more emotional. Other characteristics that clearly indigo child has is an ESP, can saw a creatures or pure materials that are not caught by the senses of ordinary vision. This advantages made an indigo children had some difficulty in socializing with the family, society and felt confused, usually they didn’t know how to act and because of that they are ussualy capped as a mockery. as coming ridicule from others. This music are trying to contribute to the society without any physical discrimination. Formulating the concept is an important patron for composer to work in the progress to make the music, the formulation of the idea are focused on the indigo phenomenon itself, how to create a music from indigo phenomenon. Step by step in are being through to create this music , starting from the contemplation and observation, survey and interview, the determination of fund tool materials, the making of conceptual framework, the rehearsal training process part I, part II, part III, part IV, and technical evaluation of the work form , Artistic, lighting and loudspeakers.